Co-delivery nanoparticles of anti-cancer drugs for improving chemotherapy efficacy - Shan-Shan Qi; Jia-Hui Sun; Hao-Han Yu; Shu-Qin Yu (Taylor & Francis Group, 2017)
To achieve superior therapeutic efficacy, the combination chemotherapy using two or more anticancer drugs in clinical practice has been generally accepted as a feasible strategy. On account of the concept of combination chemotherapy, co-delivery of anticancer drugs with nanotechnology gradually becomes a desired strategy and one of the research frontiers on modern drug delivery. In recent years, nano drug co-delivery system (NDCDS), which loads at least two anticancer drugs with different physicochemical and pharmacological properties into a combination delivery system, has achieved rapid development. NDCDS synergistically inhibited the growth of the tumor compared with the free drugs. In this review, we highlighted the current state of co-delivery nanoparticles and the most commonly used nanomaterial, discussed challenges and strategies, and prospect future development.